The Effect Of Locus Of Control And Integrity On Audit Qualitiy (Empirical Study On BPK Representative of the Riau Province) - DIAN JUWENI PUTRI (Riau International Conference on Economics, Business and Accounting, 2025)
This study aims to find empirical evidence regarding the influence of locus of control and integrity on audit quality. The population of this study is auditors who work at the Riau Provincial Representative Audit Board (BPK). The data used in this study is primary data. Sampling was carried out with a saturated sample approach, so that the entire population was used as a sample, namely 32 examiners. The hypothesis test was carried out with the help of the SPSS Version 26 statistical test device. The results of this study found that locus of control and integrity have a significant influence on audit quality. Locus of control, which reflects the level of internal control of auditors over their work, as well as high integrity of auditors has proven to be instrumental in producing quality audits. These results indicate that these two factors need attention to improve the quality of audits conducted by BPK, especially in Riau Province. Keywords: Locus of Control, Integrity, Audit Quality